2022
DOI: 10.3390/ijms23052854
|View full text |Cite
|
Sign up to set email alerts
|

The Defensive Role of Endogenous H2S in Brassica rapa against Mercury-Selenium Combined Stress

Abstract: Plants are always exposed to the environment, polluted by multiple trace elements. Hydrogen sulfide (H2S), an endogenous gaseous transmitter in plant cells, can help plant combat single elements with excess concentration. Until now, little has been known about the regulatory role of H2S in response to combined stress of multiple elements. Here we found that combined exposure of mercury (Hg) and selenium (Se) triggered endogenous H2S signal in the roots of Brasscia rapa. However, neither Hg nor Se alone worked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The microscopic photos presented herein show strong ROS induction in response to Hg (see −Hg/0 SNP versus +Hg/0 SNP) using the reagent CM-H 2 DCFDA; a mycobiont is also visible (empty black areas are algal colonies, see Figure 2 ). The same ROS stimulation has been observed in the green alga exposed to 100 µM Hg, but not Pb [ 14 ], or in plant roots exposed to Hg [ 30 ], providing evidence that Hg is more toxic than many other common metallic contaminants. It is also known that oxidative stress markers differ in lichens treated by metals in relation to morphology and even depleted H 2 O 2 content was observed after spray application of Cd [ 31 ], while immersion in Cd-enriched solutions led to enhanced ROS or H 2 O 2 formation detected by fluorescence microscopy and standard spectrophotometry [ 18 ].…”
Section: Resultsmentioning
confidence: 70%
“…The microscopic photos presented herein show strong ROS induction in response to Hg (see −Hg/0 SNP versus +Hg/0 SNP) using the reagent CM-H 2 DCFDA; a mycobiont is also visible (empty black areas are algal colonies, see Figure 2 ). The same ROS stimulation has been observed in the green alga exposed to 100 µM Hg, but not Pb [ 14 ], or in plant roots exposed to Hg [ 30 ], providing evidence that Hg is more toxic than many other common metallic contaminants. It is also known that oxidative stress markers differ in lichens treated by metals in relation to morphology and even depleted H 2 O 2 content was observed after spray application of Cd [ 31 ], while immersion in Cd-enriched solutions led to enhanced ROS or H 2 O 2 formation detected by fluorescence microscopy and standard spectrophotometry [ 18 ].…”
Section: Resultsmentioning
confidence: 70%
“…It can be clearly observed that wheat seeds are relatively insensitive to 5 mM aluminium ions and their lengths and germination percentage are almost the same with those germinated in pure water; this is probably because the low-degree stress induced by the low level of aluminium ions (5 mM) can be offset by the H 2 S produced upon the stimulation of abiotic stress. Upon exposure to 10 mM aluminium ions, the intensity of fluorescence signals enhance; this is probably because the relatively high abiotic stress inhibits the growth, and in the meantime, it also stimulates the overproduction of H 2 S to fight against the stress, 29 hence the length of the seedlings shortens slightly and around 60% of germination percentage can still be observed. However, As the concentration of aluminium ions continues to increase to 25 mM, the intensity of fluorescence decreases obviously, which may be attributed to the serious stress leading to the decline of l -cysteine desulfhydrase activity 28,30 and consequently H 2 S is underproduced in vivo in the plants that can barely fight against the stress, therefore both the length of the seedlings and the germination percentage decline obviously.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals in the soil suppress plant growth by inhibiting the uptake and movement of essential nutrients [6,7]. Intracellular accumulation of non-essential heavy metals such as Pb, cadmium (Cd), mercury (Hg), and silver (Ag) leads to the production of reactive oxygen species (ROS) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%